Réponses

2013-08-21T09:34:08+02:00

→          2 (x − 3)  =  1/4 (3x − 2) + 1/2
                2x − 6  =  3x/4 −1/2 + 1/2
         8x/4 − 3x/4  =  6
                   5x/4  =  6
                       x  =  6 × 4/5
                           =  4,8

 

        [Vérification :      2(4,8 − 3)  =  1/4(3 × 4,8 − 2) + 1/2
                                           3,6  =  3,6]

 

 

 

 

 

→          2x − 3(x + 1)  =  1 − 2x/2
               2x − 3x − 3  =  1 − x

               2x − 3x + x  =  1 + 3
                              0  =  4

           

          ce qui est absurde donc aucune solution :      x  ∈  { ∅ }

 

 

 

 

 

→          2(x − 1)  =  √2 (x + 1) − 1
               2x − 2  =  x√2 + √2 − 1
            2x − x√2  =  2 + √2 − 1
            x(2 − √2)  =  1 + √2
                       x  =  (1 + √2)∕(2 − √2)
                           =  (1 + √2)(2 + √2)/(2² − √2²)
                           =  (2 + √2 + 2√2 + √2²)/2
                           =  (4 + 3√2)/2

                           =  2 + 3√2/2

 

        [Vérification :      2 [ (2 + 3√2/2) − 1 ]  =  √2 [ (2 + 3√2/2) + 1] − 1

                                             4 + 3√2 − 2  =  2√2 + 3 × 2/2 + √2 − 1
                                                   3√2 + 2  =  3√2 + 3 − 1
                                                   3√2 + 2  =  3√2 + 2]

 

 

 

 

 

→          x − √3(x + 1)  =  2 − x
             x − x√3 − √3  =  2 − x
                   2x − x√3  =  2 + √3
                   x(2 − √3)  =  2 + √3
                              x  =  (2 + √3) / (2 − √3)
                                  =  (2 + √3)² / (2² − √3²)
                                  =  (4 + 4√3 + 3) / (1)
                                  =  7 + 4√3

 

        [Vérification :      (7 + 4√3) − √3[(7 + 4√3) + 1]  =  2 − (7 + 4√3)
                                   7 + 4√3 − 7√3 − 4 × 3 − √3  =  2 − 7 − 4√3
                                                              −5 − 4√3  =  − 5 −4√3 ]